A system of state-dependent delay differential equation modelling forest growth II: Boundedness of solutions. (August 2018) - Magal, Pierre; Zhang, Zhengyang
Abstract: In this article we consider a class of state-dependent delay differential equations which models the dynamics of the number of adult trees in forests. We prove the boundedness and the dissipativity of the solutions for a single species model and an n -species model.